2016
DOI: 10.1176/appi.ajp.2015.14121571
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Striatal Functional Connectivity as a Predictor of Response to Antipsychotic Drug Treatment

Abstract: Objective Clinical response to antipsychotic drug treatment is highly variable, yet prognostic biomarkers are lacking. The authors recently demonstrated that successful antipsychotic drug treatment alters resting-state functional connectivity of the striatum. The goal of the present study was to test whether intrinsic striatal connectivity patterns provide prognostic information and can serve as a potential biomarker of treatment response to antipsychotic drugs. Method The authors used resting-state function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
158
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(172 citation statements)
references
References 34 publications
14
158
0
Order By: Relevance
“…Investigating neurochemical differences between treatment-responsive and treatment-resistant patients may be of particular importance, as these could inform different approaches to pharmacological intervention. Neuroimaging studies may also use resting state data to investigate functional connectivity, as a recent study [84] and a review of the broader literature [48] have indicated this may have a role in predicting treatment response. In terms of genetic markers of treatment-resistant illness, psychiatric genetics as a field has moved away from the candidate-gene approach used in all genetic studies identified by the present review; future research should consider instead well-powered GWAS’s and more sophisticated models incorporating gene-environment interactions and epigenetic variation.…”
Section: Discussionmentioning
confidence: 99%
“…Investigating neurochemical differences between treatment-responsive and treatment-resistant patients may be of particular importance, as these could inform different approaches to pharmacological intervention. Neuroimaging studies may also use resting state data to investigate functional connectivity, as a recent study [84] and a review of the broader literature [48] have indicated this may have a role in predicting treatment response. In terms of genetic markers of treatment-resistant illness, psychiatric genetics as a field has moved away from the candidate-gene approach used in all genetic studies identified by the present review; future research should consider instead well-powered GWAS’s and more sophisticated models incorporating gene-environment interactions and epigenetic variation.…”
Section: Discussionmentioning
confidence: 99%
“…We excluded two APM papers (35, 36) due to the lack of meaningfully defined pre-treatment conditions (too diverse a representation of APM's), which make interpretation of the results difficult. We excluded investigations evaluating: 1) the effects of one session of cognitive training on brain function (not longitudinal) (37) and 2) baseline functional abnormalities in patients which predicted treatment outcome (38-40). (See Figure 1 for details regarding literature search and study selection).…”
Section: Methodsmentioning
confidence: 99%
“…Further, there is evidence that functional connectivity may predict response to treatment with antipsychotics (Sarpal et al, 2016) and that functional connectivity changes are correlated with alleviation of symptoms following successful treatment (Sarpal et al, 2015). …”
Section: Pharmacological Imaging and The Behavioral Effects Of Ketaminementioning
confidence: 99%